Efektivitas Implementasi Pelayanan Publik Digital: Studi Kasus Pelayanan Perpustakaan Digital Puslatbang PKASN LAN - Yuningsih, Yuyu (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2022)
One of Puslatbang PKASN LAN’s digital services is the library application which started in 2010. This application was developed internally and has been used for more than a decade. This study aims to analyze how effective this application is, the management of the library, and analyze the driving factors as well as the obstacles encountered during use. A descriptive qualitative method was used with data triangulation. Deployment of questionnaires filled by the users to find out the effectiveness of the services and interview conducted with the librarian of Puslatbang PKASN LAN. The results showed that 93.34% of users felt helped by the digital service of the Puslatbang PKASN Library which shows that the level of effectiveness is very high. The supporting factor, as well as the inhibiting factor, is the leadership's commitment to this digitizing library services. Other agencies that are willing to adopt and/or replicate this service should pay attention to some of the things, among others are (1) availability of competent human resources for library administrators such as librarians or other administrators; (2) availability of supporting infrastructure, and (3) leadership policies that support the implementation of digital services.